On the AIMD Algorithm Under Saturation Constraints - Studli, S.; Corless, M.; Middleton, R. H.; Shorten, R. (IEEE transactions on automatic control, 2017)
One of the most successful distributed resource allocation algorithms to be deployed in industry is the Additive-Increase Multiplicative-Decrease (AIMD) algorithm of Jain and Chiu. This algorithm already underpins the transport layer of the internet, and is now starting to find application in new areas in the context of Smart Grid and Smart Transportation applications. A distinguishing feature of these latter application areas, when compared with the internet, is the need to modify AIMD to account for lower and upper bounds in the resource allocated to individual agents. Our objective in this note is to demonstrate that the dynamic system arising from AIMD in this extended form has system theoretic properties similar to the classical algorithm.